Rates of achieving meaningful outcomes after undergoing minimally-invasive far lateral tubular decompression - Ameen Barghi; Anirudh Gowd; Edward Beck; Marcel Brown; Evan M. Miller; Ziyad Knio; Matthew Jamison; Tadhg O’gara (BMC Musculoskeletal Disorders)
Abstract Purpose To evaluate rates of achieving meaningful outcomes among patients undergoing far lateral tubular decompression (FLTD) for neuroforaminal stenosis. Traditional midline approaches are ineffective in treating isolated neuroforaminal stenosis. Direct decompression via a far lateral approach offers a minimally invasive, facet-sparing surgery with minimal surgical dissection. Methods Patients who underwent FLTD between January 2014 and January 2019 for isolated foraminal stenosis were included. The study collected patient demographics, perioperative data, and pre- and postoperative patient-reported outcomes (PROs). The study calculated thresholds for achieving minimal clinically important difference (MCID) on each PRO and performed logistic regression analysis to identify predictors of achieving meaningful clinical outcomes and clinical failure. Results 64 patients were included with a 2-year follow-up. The analysis showed improvement in each PRO over the 2-year period (p < 0.001 for all). 90.2% of patients achieved MCID for at least one PRO, with the VAS leg pain having the highest achievement rate at 79.7%. During the follow-up period, 17.2% required additional surgery. Increased severity of preoperative symptoms was associated with a greater likelihood of achieving MCID in all three PROs (p < 0.05, each). The presence of spondylolisthesis was associated with decreased odds of achieving MCID by ODI (p = 0.04). Increased operative time was associated with increased odds of achieving MCID by ODI (p = 0.03). No variables were associated with revision surgery. Conclusions FLTD is an effective treatment option for direct decompression of foraminal and extra foraminal stenosis in well-indicated patients. Most patients achieved MCID two years from surgery, with more severe symptoms having a greater likelihood of improvement, particularly with radicular pain. Further research should be performed on patients with spondylolisthesis to prescribe treatment resulting in maximal benefit. Level of evidence 4.